The Effect of Instruction Through Mobile Phone-Based Virtual Networks on the Learning Rate of Students with Visual Impairment - Zabihollah Allahi; Morteza Bakhtiarvand; Maryam Rajabiyan Dehzireh (Randwick International of Education and Linguistics Science Journal, 2020)
This study aims at investigating the effects of instruction using mobile phone based virtual networks on the rate of learning of students with visual impairment. This study utilized a quasi-experimental approach, which was performed among male students suffering from visual impairment in their second grade of high school in Iran. The sample size consisted of 52 students with visual impairment (26 in experimental group and 26 in control group) who had cell phones and volunteered to participate in the test. The experimental group was taught through WhatsApp social network while the control group received regular classroom teachings. The data was collected using a researcher made English language test. The findings of the study revealed that the instruction through the virtual networks has a positive effect on the increase of learning rate in students with visual impairment. The results from this study would be useful to instructional designers, specialists, special education teachers and learners who wish to use cell phones for the blind.